Analysis of the cytotoxic mechanism exhibited by methanolic tuber extract of medicinal plant Corallocarpus epigaeus in HeLa cells - Akshay G M
The Present study has evaluated the anticancer potential of methanolic tuber extracts of the plant Corallocarpus epigaeus (C. epigaeus) and elucidated the cytotoxic mechanism exhibited by the tuber extract in HeLa cells. The IC50 value of methanolic tuber extracts of C. epigaeus in HeLa cells was found to be around 50ng/ml by MTT analysis. In vitro scratch assay and clonogenic assay showed positive results for the anti-proliferative of methanolic tuber extract of C. epigaeus in HeLa cells. Evaluation of the cytotoxic mechanism exhibited by the methanolic tuber extract by immunoblot analyisis of PARP cleavage revealed that the tuber extract kills HeLa cells by the induction of apoptosis.